Respostas ecofisiológicas e bioquímicas de duas cultivares de tomate (Lycopersicum esculentum MILL.) cultivadas em sistemas de agricultura natural e convencional - Tavares, Nelson Salgado (2006)
Today the world has interest in consuming healthful foods without chemical residues to maintain both the health of the human being and the planet Earth. The alterations that occur in tomato plants (Lycopersicum esculentum Mill.) cultivated in both natural and conventional systems of production had been assessed in two cultivars Gaúcho and Special Salada in Vila Velha, Espírito Santo, Southeast of the Brazil. The leaves and the fruits had been analyzed in the laboratories of official institutions, where was determined the weight, volume, humidity, dry matter, ashes, dry matter without ashes, total protein, free amino acids, total soluble solids, phenolic compounds, nitrate, the loss of water, time of shelf life and the macro and micronutrients. In the field, both photosynthesis and chlorophyll had been measured. It did not have production in the first plantation from natural farming. However, after four cultivations repeated in the same seedbeds, the fourth production was 21 t/ha. The first production of fruits of the conventional system was 56 t/ha and 167% greater than natural farming. The increase of the productivity in the natural farming was dependent of the capacity of the tomato plants adapt itself to the environment without chemical fertilizer and without poisons. The total phenol production within leaves and fruits of the tomato cultivated in system of natural farming was 36.86% greater than plants of tomato produced in the conventional system, while the total free amino acid was 305.53% greater in leaves and fruits growing in the conventional system. The plants of the natural farming had had greater water use efficiency (WUE) to fix CO2. The plants of the conventional system had used up 714 mL of water to fix 1.0 g CO2, while the plants of the natural farming had used up 321 mL to fix 1.0 g CO2. The plants of the system of natural farming had produced more vegetal matter for unit of natural resources than the plants of the system of conventional system. The fruits of the natural farming had had 16.76% more potassium, the biggest time of shelf life and had kept more characteristics of quality per 6 days than fruits of the conventional system.